Current Status of Faculty Development Events in Different Medical Institutions of Bangladesh - Ahmed, Wakil; Shipu, Zinat Rehana; Hossain, Syed Zakir; Afroza, Syeda; Talukder, Md Humayun Kabir (Bangladesh Journal of Medical Education, 2020)
Objective: To assess the current status of faculty development events in different Medical institutions of Bangladesh among the medical teachers. Methods: This cross sectional study was carried out in four medical Institutions situated in Dhaka city and outside Dhaka. Total respondents were 120 teachers working in medical colleges and institute. Opinion of one hundred teachers working in preclinical, para clinical and clinical departments were collected by self administered semi structured questionnaire. Twenty (20) teachers were selected for in depth interview. Results: Study revealed that thirty eight percent of medical teachers attended in Faculty Development (FD) activity within one year whereas sixty two percent did not participate in any FD activity. Among the attended teachers in FD activity 65.8% teacher attended by self initiative and 63.2% were by self funding. All of them mentioned that it was beneficial to them. Twenty percent of medical teachers told in in depth interview that they have no clear cut idea about faculty development activity. Among the respondents, majority (80%) in in-depth interview and 68% in questionnaires) of the teachers thought that the existing activity in their institution is effective to some extent and few respondents (20%) in in-depth and 3% in questionnaires) thought that it is very effective. They also highlighted the areas which should be emphasized for faculty development includes: assessment, professional development, teaching material development etc. Majority of teachers in both the groups in in-depth interview (80%) and in-structured questionnaires (99%) opined that a well organized faculty development program is a needed for medical teachers. Conclusion and recommendation: Existing faculty development activities in different institutions are not very effective. A well-organized faculty development program is a need for medical teachers. A proper policy level guidelines for at periodic training for the teachers can improve faculty development of different institutions. Bangladesh Journal of Medical Education Vol.11(2) 2020: 14-20